Bibliometric study on the knowledge graph of immunotherapy for head and neck cancer - Wang, Ji; Gong, Zhengpeng; Yu, Ming (Frontiers in Oncology, 2023)
Background: Head and neck squamous cell carcinoma (HNSCC) is a frequent malignant tumor with a high death rate, particularly in individuals with advanced local stage, recurrence, and metastasis. Significant progress has been made in recent years in treating local advanced stage recurrence and metastasis as a result of the use of immunotherapy medicines.. No bibliometric studies, however, have been published. The purpose of this study is to analyze and forecast trends and hotspots in this field using bibliometric analysis of HNSCC immunotherapy to gain a better understanding of the current state and future direction of HNSCC immunotherapy.Methods: All articles and publications on immunotherapy of HNSCC are extracted from the Web of Science Core Collection (WoSCC). Bibliometrics is used to analyze the results of scientific research, including countries/regions, institutions, authors (cited authors), journals (cited journals), references, and to clarify the research hotspots and future research trends in this research field.Results: In total,1049 English articles published between 2000 and 2021 were collected, and the number of articles increased rapidly from 2016. The United States has the largest number of publications(n=430,40.9%), followed by China and Germany. The one that published the most papers was the University of Pittsburgh (n=81, 7.72%). ROBERT L FERRIS ranks first among the top ten authors and cited authors. Oral Oncology is the most prolific academic journal on immunotherapy of HNSCC[( n=61,5.81%; impact factor (2020) = 5.337]. The aggregation and recognition of key nodes in the co-reference network indicate a shift in the field of immunotherapy for HNSCC. The initial hotspots are mainly "interleukin 2", " lymphocyte", " in vivo", "phase I", and " dendritic cell "but in recent years, the focus has shifted to " nivolumab ", " pd1 blockade ", "landscape", " hpv "," pd l1" and " pembrolizumab ".Conclusion:Advances in immunotherapy are drawing more attention to HNSCC. Immunotherapy for head and neck cancer is currently being tested in combination with other treatment approaches, such as local therapy and targeted therapy, in order to better understand the immune landscape of the disease and identify patients who are most likely to benefit from immunotherapy.